Pembuatan E-KTP di Disdukcapil Kabupaten Karawang pada Masa Pandemi Covid-19: Tinjauan Kualitas Pelayanan Publik - Inka Farjela; Lukmanul Hakim; Indra Aditya (Peneliti.net, 2022)
The Department of Population and Civil Registration of Karawang Regency is one of the Regional Apparatus Organizations in Karawang Regency which has the authority to administer Population Administration. This paper aims to describe the quality of public services organized by the Disdukcapil Karawang Regency in providing services for making electronic ID cards during the Covid-19 pandemic. This paper is analyzed using a qualitative method, the qualitative method emphasizes the problem aspects of the obstacle factors in the process of making an e-KTP during the Covid-19 pandemic, while the descriptive method is used to analyze the data that the author has obtained from the Disdukcapil Karawang Regency. Disdukcapil Karawang Regency as a service provider for the community is constrained during the Covid-19 pandemic situation. To analyze and determine the quality of population services during the Covid-19 pandemic, the authors collect data obtained through observation and interviews based on the dimensions of the quality of public services according to Zeithaml in Boediono (2003:114), namely, tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee), and empathy (empathy). By using qualitative research methods, it is hoped that the authors will be able to produce data in the form of words or writings that are descriptive in nature in improving the quality of population administration services during the Covid-19 pandemic at the Disdukcapil, Karawang Regency.